2005
DOI: 10.1590/s1516-89132005000300005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships among species of the genus Bothrops based on RAPD markers

Abstract: The genetic relationships among 11 species of Bothrops found in Brazil were determined using random amplified fragment (RAPD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In general, phylogenetic relationships within Bothrops, as previously recognized, have been analyzed mostly using molecular evidence (e.g., Salomão et al, 1997Salomão et al, , 1999Wüster et al, 1999;Parkinson, Campbell and Chippindale, 2002;Wüster et al, 2002;Grazziotin and Echeverrigaray, 2005;Castoe and Parkinson, 2006). Werman (1992) and Gutberlet and Harvey (2002) incorporated anatomical features in their analyses, but these studies included several genera of Neotropical pitvipers and only a few species of Bothrops.…”
Section: Introductionmentioning
confidence: 99%
“…In general, phylogenetic relationships within Bothrops, as previously recognized, have been analyzed mostly using molecular evidence (e.g., Salomão et al, 1997Salomão et al, , 1999Wüster et al, 1999;Parkinson, Campbell and Chippindale, 2002;Wüster et al, 2002;Grazziotin and Echeverrigaray, 2005;Castoe and Parkinson, 2006). Werman (1992) and Gutberlet and Harvey (2002) incorporated anatomical features in their analyses, but these studies included several genera of Neotropical pitvipers and only a few species of Bothrops.…”
Section: Introductionmentioning
confidence: 99%
“…Ro et al (2007) obtained good results when they used RAPD aiming to differentiate the strains of Pleurotus eryngii. The technique has been used in the studies with Verticillium fungicola, with excellent results (Del Carmen et al, 2002; and by other researchers for works with many other organisms, always differentiating very close taxonomic groups (Grazziotin et al, 2005;Muok et al, 2007;Tang et al, 2007;Rajwana et al, 2008;Solouki et al, 2008;Venkatachalam et al, 2008;Tsvelikas et al, 2009). The primers used in this study, however, were not enough to measure with accuracy the genetic distance of the strain CC-63 (Chinese strain), and it is suggested could be use other primers for analyzing or complete the differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…At the border between Roraima and Venezuela, where the patient comes from, the most common snake is the viper B. atrox [6,24]. Besides the patient who confirmed that the snake was a lancehead, clinical features were in agreement with viper venom-induced effects, as most literature shows that vipers can cause acute kidney injury and coagulopathy [4,5,7].…”
Section: Case Presentationmentioning
confidence: 99%
“…Bothrops , Crotalus , Lachesis, and Micrurus are the medically most important snake genera in Brazil, with the Bothrops genus (lancehead pitvipers) being responsible for the majority of bites (90%) and snakebite related deaths (0.3%) within the Brazilian Amazon [ 3 , 4 ]. Among the 30 species of Bothrops snakes that are found in Brazil [ 5 , 6 ], Bothrops atrox (common lancehead, Amazonian jararaca) is considered to be the medically most important species due to its high level of adaptation and wide distribution in both rainforests and populated areas [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%